The effect of audit delay, audit fee and audit opinion on auditor switching: Empirical study of energy sector companies on the Indonesia Stock Exchange in 2020-2023 - Ningrum, Aisyah Eka; Ningrum, Endah Prawesti; Nuryati, Tutty; Yulaeli, Tri (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: The energy sector requires large long-term investments for infrastructure and technology development. Therefore, transparency in financial reporting is very important to provide a clear picture of the company's financial performance and prospects for investors. Methods: This study uses a quantitative approach with purposive sampling method. There were 58 companies that met the research criteria and 4 years of observation with a total of 232 samples. Data analysis used descriptive statistical tests, binomial logistic regression tests and hypothesis testing. Findings: The results of this study indicate that audit delay and audit opinion affect auditor switching. In contrast, audit fees show no effect on auditor switching. Conclusion: Audit delay and audit opinion are proven to have an effect on auditor switching in energy sector companies on the IDX, while audit fees do not show a significant effect. These results indicate that the time factor and the quality of the opinion are more considered than the cost in the decision to change auditors. Novelty/Originality of this Article: This study contributes to the limited literature on auditor switching by focusing on the energy sector in Indonesia, which requires long-term investments and transparent financial reporting.